Karl Polanyi on strategy: The effects of culture, morality and double-movements on embedded strategy. (December 2020) - Faulconbridge, James R.; Muzio, Daniel
Highlights: Explores theoretical links between institutions, strategy and Karl Polanyi's work. Reviews the activities of English law firms in Italy as a case study. Identifies links between strategy, markets, the state and society. Conceptualises strategy as embedded, with legitimacy in economy and society key. Abstract: Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi's ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi's work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi's work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi's ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy's legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the 'double movement' Polanyi discusses and ensure strategies serve the interests of society as well as those of the market.